Pengaruh Pemakaian Ukuran Batu Bata terhadap Harga Satuan Pasangan Dinding pada Bangunan Sederhana - Sahrul Harahap; Suryanti Suraja Pulungan (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2025)
The evolving construction industry requires a deep understanding and mastery of aspects related to construction, particularly in terms of costs, which are a key factor in project execution. Cost estimation or the Budget Plan (RAB) is essential as a guide during the construction process. This study aims to analyze the effect of brick size on the unit price of wall installation in simple buildings. The study was conducted around the city of Padangsidempuan, taking several samples of brick sizes commonly used in simple building construction. Data calculation procedures used AHSP (Analysis of Unit Price Work) based on the Indonesian Ministry of Public Works and Housing Regulation No. 1 of 2022. The results of the study show that the smaller the brick dimensions, the higher the unit price for the installation of red brick walls.